Bridging the digital education gap through Values-Based Learning: A transformative education model in East Nusa Tenggara, Indonesia - Yosua Yan Hariyanto; Jefrit Johanis Messakh; Degunias Ton (Digital Theory, Culture & Society, 2026)
Digital educational inequality in Eastern Indonesia, particularly in East Nusa Tenggara (NTT), remains a persistent structural challenge shaped not only by inadequate infrastructure and limited technological access but also by the insufficient integration of moral, social, and spiritual values into educational practices. This study examines how the Value- Based Learning (VBL) approach can reduce educational disparities by fostering character development, social awareness, and sensitivity to local cultural contexts. Using a qualitative descriptive case study, the research was conducted in several schools across East Nusa Tenggara. Data were collected through field observations, in-depth interviews with teachers and school principals, and analyses of learning documents, and were analyzed thematically. The findings reveal that VBL enhanced students' learning motivation, social engagement, empathy, and their ability to connect academic knowledge with everyday life. Compared with predominantly technocratic and cognitively oriented learning models, VBL demonstrated greater responsiveness to local socio-cultural contexts. These findings highlight the potential of value-based education to promote humanization and social empowerment and suggest that educational policies should strengthen the integration of humanistic values, local culture, and spirituality into curriculum development, particularly in marginalized regions.